Strong homeostatic TCR signals induce formation of self‐tolerant virtual memory CD8 T cells. (11th May 2018) - Drobek, Ales; Moudra, Alena; Mueller, Daniel; Huranova, Martina; Horkova, Veronika; Pribikova, Michaela; Ivanek, Robert; Oberle, Susanne; Zehn, Dietmar; McCoy, Kathy D; Draber, Peter; Stepanek, Ondrej
Abstract: Virtual memory T cells are foreign antigen‐inexperienced T cells that have acquired memory‐like phenotype and constitute 10–20% of all peripheral CD8 + T cells in mice. Their origin, biological roles, and relationship to naïve and foreign antigen‐experienced memory T cells are incompletely understood. By analyzing T‐cell receptor repertoires and using retrogenic monoclonal T‐cell populations, we demonstrate that the virtual memory T‐cell formation is a so far unappreciated cell fate decision checkpoint. We describe two molecular mechanisms driving the formation of virtual memory T cells. First, virtual memory T cells originate exclusively from strongly self‐reactive T cells. Second, the stoichiometry of the CD8 interaction with Lck regulates the size of the virtual memory T‐cell compartment via modulating the self‐reactivity of individual T cells. Although virtual memory T cells descend from the highly self‐reactive clones and acquire a partial memory program, they are not more potent in inducing experimental autoimmune diabetes than naïve T cells. These data underline the importance of the variable level of self‐reactivity in polyclonal T cells for the generation of functional T‐cell diversity. Synopsis: Virtual memory T cells are formed from self‐reactive CD8 + T cells in a process regulated by CD8‐Lck. Despite their self‐reactivity and features of memory T cells, virtual memory T cells did not show a strong potential to trigger an autoimmune pathology. Virtual memory CD8 + T cells are formed from relatively highly self‐reactive peripheral T cells. Virtual memory T cells exhibit an intermediate stage between naïve and true antigen‐experienced T cells. Virtual memory, true antigen experienced memory, and naïve T cells show functional differences upon activation. Virtual memory T cells do not show higher potential to induce experimental tissue pathology than naïve T cells on a per cell basis. Abstract : T‐cell receptor signalling can induce formation of self‐reactive CD8 + cells with features of memory T cells, which however do not show strong potential for triggering autoimmune pathology.